Pull Factors for Event Delegates Moderating Effect Of Cultural Tourism Attraction - Yuniati, Nining (Publisher Cv. Inara, 2024)
This study seeks to explore the pull factors that influence delegates' decision to attend an event. This research also involves the factor of cultural tourism attraction as a moderating variable. It is well known that Yogyakarta as the research location is a city rich in culture, there are many cultural attractions that are favored such as heritage sites, indigenous people's lives, handicraft products, traditional culinary, and a number of other local cultural products. By using Structural Equation Model analysis and involving 190 respondents, namely delegates who attended various events in Yogyakarta, from the results of the study it was found that the pull factors namely accessibility, event organizer (OC), accommodation, venue, price and cultural tourism attraction jointly influenced the decision of delegates to attend the event. Cultural tourism attraction is able to moderate the overall pull factor. The strength of culture that is able to moderate the overall attraction factor indicates that culture is very strong as a novelty event and is a key variable for destinations so that it is attractive to host events.